2020
DOI: 10.18632/aging.103025
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells transplantation alleviates brain injury after intracerebral hemorrhage in mice through the Hippo signaling pathway

Abstract: Intracerebral hemorrhage (ICH) is a common acute nervous system disease with high mortality and severe disability. Mesenchymal stem cells (MSCs) have been reported to promote neurogenesis and to alleviate side effects in areas of brain injury areas. The Hippo pathway regulates diverse cellular processes, including cell survival, proliferation, differentiation, and organ size. Here, we found that transplantation of bone marrow MSCs (BM-MSCs) into the brains of mice could alleviate ICH-mediated injury and protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In mammals, the activation of the Hippo pathway leads to the inactivation of Yes-associated protein (YAP) by large tumor suppressor 1/2 (LATS1/2)-mediated direct phosphorylation. Contrariwise, dephosphorylation of YAP results in its transport into the nucleus and its succeeding interaction with TEA/ATTS domain (TEAD), forkhead box protein O1 (FOXO1), and other transcription factors, and therefore can exert cell proliferation, organ growth, and stem cell self-renewal [ 147 ]. Other studies on murine LPS models demonstrated that transplantation of murine BM-MSCs with downregulated Hippo pathways led to the intensified retention of murine MSC in ARDS lung tissue and their differentiation into alveolar epithelial type II (AE2) cell as a supporter of the alveolus [ 120 ].…”
Section: Application Of Msc Therapy In Immune-mediated Disordersmentioning
confidence: 99%
“…In mammals, the activation of the Hippo pathway leads to the inactivation of Yes-associated protein (YAP) by large tumor suppressor 1/2 (LATS1/2)-mediated direct phosphorylation. Contrariwise, dephosphorylation of YAP results in its transport into the nucleus and its succeeding interaction with TEA/ATTS domain (TEAD), forkhead box protein O1 (FOXO1), and other transcription factors, and therefore can exert cell proliferation, organ growth, and stem cell self-renewal [ 147 ]. Other studies on murine LPS models demonstrated that transplantation of murine BM-MSCs with downregulated Hippo pathways led to the intensified retention of murine MSC in ARDS lung tissue and their differentiation into alveolar epithelial type II (AE2) cell as a supporter of the alveolus [ 120 ].…”
Section: Application Of Msc Therapy In Immune-mediated Disordersmentioning
confidence: 99%
“…Our results are consistent with previous studies. After transplantation of MSCs with IronQ in ICH mice, astrocytes underwent astroglial-mesenchymal phenotype switching and became capable of proliferating, and were protected from apoptosis, similarly to previous studies (51,53). However, some studies have suggested that an excessive proliferation of reactive astrocytes leads to glial scar formation, which is harmful to axon growth and neural network reconstruction (54,55).…”
Section: Discussionsupporting
confidence: 69%
“…Astrocytes, one of the primary components of glial cells, have also been confirmed to have a reparative function in the injured brain tissue after ICH ( Zhang et al, 2006 ; Chen et al, 2020b ), although adequate research is not recorded. After transplantation of MSCs in ICH mice, astrocytes underwent astroglial–mesenchymal phenotype switching and became capable of proliferating and were protected from apoptosis via downregulation of p-MST1 and p-YAP ( Chen et al, 2020b ). Together, the Hippo pathway-mediated favorable impacts of MSCs can be recognized as a unique therapeutic target in ICH injury ( Chen et al, 2020b ).…”
Section: Mechanisms Of Mesenchymal Stem Cells In Intracerebral Hemorr...mentioning
confidence: 99%
“…After transplantation of MSCs in ICH mice, astrocytes underwent astroglial–mesenchymal phenotype switching and became capable of proliferating and were protected from apoptosis via downregulation of p-MST1 and p-YAP ( Chen et al, 2020b ). Together, the Hippo pathway-mediated favorable impacts of MSCs can be recognized as a unique therapeutic target in ICH injury ( Chen et al, 2020b ). Experiments performed by Chen et al (2020a) also found that transplanting BMSCs led to an elevation of glial fibrillary acidic protein (GFAP), a biomarker of astrocytes, and the level of expression and improved astroglial–mesenchymal phenotype switching and anti-apoptotic abilities through the Cx43/Nrf2/HO-1 axis.…”
Section: Mechanisms Of Mesenchymal Stem Cells In Intracerebral Hemorr...mentioning
confidence: 99%